1999
DOI: 10.1016/s0006-3495(99)77149-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of N2B Cardiac Titin’s Extensibility

Abstract: Titin is a giant filamentous polypeptide of multidomain construction spanning between the Z- and M-lines of the cardiac muscle sarcomere. Extension of the I-band segment of titin gives rise to a force that underlies part of the diastolic force of cardiac muscle. Titin's force arises from its extensible I-band region, which consists of two main segment types: serially linked immunoglobulin-like domains (tandem Ig segments) interrupted with a proline (P)-, glutamate (E)-, valine (V)-, and lysine (K)-rich segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 31 publications
3
83
0
1
Order By: Relevance
“…The N2B region of titin extends mostly toward the upper limit of the physiological sarcomere length of cardiac muscle (25,44). Our findings highlight what we believe is a novel role for FHL1 in modulating titin N2B function and sarcomere extensibility at the upper limits of the physiological sarcomere length, a state that could be physiologically reached in vitro through acute stretch and in vivo by pressure overload.…”
Section: Discussionmentioning
confidence: 50%
“…The N2B region of titin extends mostly toward the upper limit of the physiological sarcomere length of cardiac muscle (25,44). Our findings highlight what we believe is a novel role for FHL1 in modulating titin N2B function and sarcomere extensibility at the upper limits of the physiological sarcomere length, a state that could be physiologically reached in vitro through acute stretch and in vivo by pressure overload.…”
Section: Discussionmentioning
confidence: 50%
“…Analysis of the N2B-KO mice allowed us to test the hypothesis that the N2B unique sequence eliminates the necessity for unfolding of Ig domains under physiological conditions (3). In absence of the N2B element, we found that the extension of PEVK and tandem Ig segments is increased (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, cardiac titin contains a third extensible region, the N2B element (2), which is absent in skeletal muscle. The N2B region extends greatly toward the upper limit of the physiological sarcomere length of cardiac muscle (3,4). It has been suggested that this extension reduces the steepness of the passive forcesarcomere length relation, decreasing the likelihood of the unfolding of Ig domains (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiac muscle, the extension of the N2B sequence that occurs in the upper limit of the physiological SL decreases passive force and presumably prevents the unfolding of the Ig segment [36][37][38]. A consensus still has not been achieved on whether the unfolding/refolding of Ig segments occurs within the physiological SL.…”
Section: Mechanism Of Passive Force Generation On Titin Extensionmentioning
confidence: 99%